Exploring the Evolution of Green Sukuk Research: Trends, Themes, and Policy Implications for Sustainable Islamic Finance - Liya Setiawati (International Forum of Researchers and Lecturers, 2025)
This study explores the intellectual and thematic evolution of green sukuk research within Islamic sustainable finance from 2015 to 2025. Using a hybrid methodological design that integrates the PRISMA-guided Systematic Literature Review with Watase Uake network analysis, the study identifies 17 core Scopus-indexed articles that collectively define the field’s conceptual and empirical development. Results reveal a three-phase evolution: (1) a formative stage emphasizing ethical legitimacy and Sharia compliance; (2) a transitional phase integrating pricing efficiency, market risk, and policy frameworks; and (3) a maturity phase characterized by econometric modeling, behavioral-finance integration, and sustainability governance. Thematic clusters extracted from bibliometric mapping include financial performance and market dynamics, institutional legitimacy and policy frameworks, behavioral intention and investor psychology, and technological innovation and ESG disclosure. Despite methodological advancement, the literature remains geographically concentrated in Malaysia and Indonesia and exhibits theoretical fragmentation across behavioral, financial, and institutional models. Findings highlight key research gaps involving contradictory evidence on yield–risk relationships, inconsistent behavioral determinants of investment intention, and insufficient integration of moderating or mediating mechanisms. The study advances theoretical pluralism by connecting the Theory of Planned Behavior (TPB), Institutional and Legitimacy Theory, and Resource-Based View (RBV) into an integrated model explaining how legitimacy, behavior, and strategic capability jointly drive green sukuk adoption. Policy implications emphasize the need for harmonized regulation, behavioral incentives, and digital transparency to strengthen credibility and accelerate sustainable-finance transformation in line with SDGs 7 and 13.